Analysis of the Effect of HDI and Road Length Infrastructure Development on Improving Economic Inequality in Eight Districts of the Region La Pago Tradition - Weya, Ince; Sirojuzilam, Sirojuzilam; Syafi’i, M.; Ruslan, Dede (Journal of International Conference Proceedings, 2023)
This study aims to analyze the effect of human development index and road length infrastructure development, on the improvement of economic inequality as measured by general publicationh for the period 2013-2022. Secondary data is needed to provide an explanation or answer to the research question. The data analysis model used in this study uses a panel data model with a linear regression approach (OLS). The results show that HDI (X1) has a positive effect on improving economic inequality (Y), with a regression coefficient value of 0.003326, and is significant, with a value of Prob. = 0.0000 < 0.05. Road length (X2) has a positive effect on improving economic inequality (Y), with a regression coefficient of 0.00000143 or 1.43E- 06, but not significant, with a Prob. = 0.2974 > 0.05.